Principles of physics - Serway, Raymond A. (Brooks/Cole Cencage Learning, 2013)
PRINCIPLES OF PHYSICS features a concise approach to traditional topics, an early introduction to modern physics, and integration of physics education research pedagogy, as well as the inclusion of contemporary topics throughout the text. This revision of PRINCIPLES OF PHYSICS also contains a new worked example format, two new Contexts features, a revised problem set based on an analysis of problem usage data from WebAssign, and a thorough revision of every piece of line art in the text